A New Species of Black Mildew Causing Fungus Meliola konniensis (Meliolales) from Agasthyamalai Biosphere Reserve, India - Gokul, Gopinathan Nair; Thomas, Jacob (Phytotaxa, 2022)
A new species of black mildew causing fungus infecting Aglaia perviridis (Meliaceae) collected from Southern Western Ghats of Kerala State, India is described and illustrated. Simple straight setae with variously dentate apex and opposite antrorse appressoria having apex of head cells attenuated are the features which distinguish the species from other Meliola biotrophs associated on the host family Meliaceae. This is the third species of Meliola reported infecting the host genus Aglaia from Western Ghats of India.